Angela Corder: capstone - Corder, Angela, artist (Colorado State University. Libraries, 2016)
The artist's statement: Problem solving through intricate design has always been a passion of mine, hence why I further pursued an education in graphic design. I believe the graphic design department at Colorado State University has helped me create a diverse palette of coherent consistency. I am fascinated by minimalism and try to incorporate such techniques into my work. I believe less is more with all design applications. And Artist Statements.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design